2014
DOI: 10.5511/plantbiotechnology.14.1002a
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloid transporters in plants

Abstract: Plants produce a multitude of secondary metabolites, including alkaloids with biological activities, and many alkaloids have been used for medicinal purposes. The biosynthetic enzymes and genes involved in alkaloid metabolic pathways exhibit divergent localizations, implying that alkaloid metabolites, including pathway products and intermediates, travel from organelle to organelle, cell to cell, and organ to organ. Biochemical studies have indicated that specific transporters move these metabolites. Indeed, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 76 publications
(106 reference statements)
0
26
0
Order By: Relevance
“…Recently, it was revealed that a member of the NPF transporter family was related to strictosidine transport and other members of the NPF family have been implicated in iridoid glucoside transport (Larsen et al, 2017;Payne et al, 2017). It has also been reported that various transporters may be involved in the transport of alkaloids (Carqueijeiro et al, 2013;Shitan et al, 2014). Further studies are needed to clarify how these compounds distribute between the different cell types in C. roseus, and how the site of biosynthesis may differ from the site of accumulation.…”
Section: Cell-specific Localisation Of Tias In Leaf Tissuementioning
confidence: 99%
“…Recently, it was revealed that a member of the NPF transporter family was related to strictosidine transport and other members of the NPF family have been implicated in iridoid glucoside transport (Larsen et al, 2017;Payne et al, 2017). It has also been reported that various transporters may be involved in the transport of alkaloids (Carqueijeiro et al, 2013;Shitan et al, 2014). Further studies are needed to clarify how these compounds distribute between the different cell types in C. roseus, and how the site of biosynthesis may differ from the site of accumulation.…”
Section: Cell-specific Localisation Of Tias In Leaf Tissuementioning
confidence: 99%
“…37) For further detailed information about alkaloid transport, please refer to previous reviews. 45,46) I.ii. Phenolic compounds Phenolic compounds have at least one aromatic ring with one or more hydroxyl substituents, and consist of several subgroups, e.g.…”
Section: II Alkaloidsmentioning
confidence: 99%
“…To date, the plant alkaloid transporters are mainly characterized into the ATP-binding cassette (ABC) protein, multidrug and toxic compound extrusion (MATE), and purine permease (PUP) families. Some transporters were found to be required for the efficient biosynthesis of alkaloids in plants [ 45 ]. In tobacco, several alkaloid transporter genes have been identified, such as tobacco jasmonate-inducible alkaloid tranporter1 ( Nt - JAT1 ), Nt - JAT2 , tobacco nicotine uptake permease1 ( Nt - NUP1 ), NtMATE1 and NtMATE2 [ 46 50 ].…”
Section: Resultsmentioning
confidence: 99%